The Physical Discourse of Fan Fiction - Hodunok Zoriana (Психолінгвістика, 2018)
The research of physical discourse, typical characters, stereotypical gender roles of fan fiction’s texts, based on “Harry Potter”, “Supernatural”, “The Song of Ice and Fire”/“The Game of Throne”, is realized in the article. The author uses Psycholinguistics (Frame Method and Free Associative Experiment), Hermeneutics, some elements of Comparative analysis to describe the main characteristics of the personages and explain peculiarities of their sexual interactions.